Post-activation performance enhancement does not occur following a large hand-paddles and parachute-resisted warm-up routine in collegiate swimmers - Santiago Soares Bufalo; Gabriel Fontanetti; Renan Vieira Barreto; Gabriel Rocha Benazzi; Rubens Correa Junior; Victor Marangoni; Natália de Menezes Bassan; Benedito Sérgio Denadai; Camila Coelho Greco; João Paulo Vilas-Boas; Leonardo Coelho Rabello de Lima (Frontiers Media S.A., 2023)
Our aim was to investigate if using a warm-up routine that included parachute-resisted sprints with large hand-paddles improves 50 m freestyle performance in trained collegiate swimmers. Twelve swimmers (23.9 ± 2.2 years, 179 ± 7 cm, 77.1 ± 10.6 kg) participated in the study and completed two 50-m freestyle races, each preceded by a different warm-up routine, either control (CON) or experimental (EXP). The warm-up routines consisted of 500 m of swimming at self-selected speed, followed by four 10 s sprints with 1 min rest intervals. During EXP, sprints were performed using large hand-paddles and a swimming parachute, while during CON, sprints were performed freely. Performance and technique were assessed during the 50 m freestyle races. We found no significant differences in 25- and 50 m performance times (CON: 12.6 ± 0.8 vs. EXP: 12.5 ± 0.8 s, ES = 0.125; and CON: 26.8 ± 1.6 vs. EXP: 26.7 ± 1.7 s, ES = 0.06, respectively) between the two conditions. Mean stroke length (CON: 2.04 ± 0.21 vs. EXP: 2.02 ± 0.22 m·cycle−1, ES = 0.09), stroke frequency (CON: 55.4 ± 5.3 vs. EXP: 56.3 ± 5.2 cycles s−1, ES = 0.17), and propulsive time (CON: 0.62 ± 0.07 vs. EXP: 0.61 ± 0.06 s, ES = 0.15) were also not different between conditions. It is possible that the CON warm-up routine induced the priming effects that lead to PAPE, or that the EXP warm-up routine primed the athletes further but also induced greater fatigue, resulting in no significant effects on swimming performance. Our findings suggest that parachute-resisted sprints with hand-paddles during warm-up do not enhance 50 m freestyle swimming performance in trained collegiate swimmers. Coaches and practitioners should consider exploring different warm-up protocols to identify what works best for their athletes.